2020
DOI: 10.1088/2053-1591/ab6c09
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical transformation of black phosphorous to phosphorene quantum dots: effect of nitrogen doping

Abstract: We present a comparative analysis of the structural and optical properties of electrosynthesized PQDs, a new class of size-tunable luminescent materials and their nitrogen doped counter parts(NPQDs). Nitrogen doping onto phopshorene lattice could be realized in situ at room temperature using either nitrogen containing electrolyte and/or supporting electrolyte in the solution. An increased quantum efficiency as well as redox behavior has been observed for PQDs upon nitrogen doping and a critical analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Valappil et al in their work developed an electrochemical method of single‐step BP doping. [ 119 ] It was shown that electrochemical exfoliation of BP at high cathodic potentials (−2 V) in the presence of Bu 4 NBF 4 in MeCN leads to the formation of N‐doped BPQDs.…”
Section: Functionalization and Modification Of Bpmentioning
confidence: 99%
“…Valappil et al in their work developed an electrochemical method of single‐step BP doping. [ 119 ] It was shown that electrochemical exfoliation of BP at high cathodic potentials (−2 V) in the presence of Bu 4 NBF 4 in MeCN leads to the formation of N‐doped BPQDs.…”
Section: Functionalization and Modification Of Bpmentioning
confidence: 99%